2017
DOI: 10.1007/s10714-017-2186-y
|View full text |Cite
|
Sign up to set email alerts
|

Scalar field collapse with an exponential potential

Abstract: An analogue of the Oppenheimer-Synder collapsing model is treated analytically, where the matter source is a scalar field with an exponential potential. An exact solution is derived followed by matching to a suitable exterior geometry, and an analysis of the visibility of the singularity. In some situations, the collapse indeed leads to a finite time curvature singularity, which is always hidden from the exterior by an apparent horizon.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…For example, the seminal work of Christodoulou [39] showed that a naked singularity can occur in the spherical collapse of a scalar field, while Choptuik [40] developed a numerical study for a massless scalar field considering a family of solutions with the property that a critical parameter, p * , indicates the formation of black holes. Since then several works studied the critical behavior and the properties of the gravitational collapse of scalar fields [41][42][43][44][45][46][47][48].…”
Section: Generalized Brans-dicke Theoriesmentioning
confidence: 99%
“…For example, the seminal work of Christodoulou [39] showed that a naked singularity can occur in the spherical collapse of a scalar field, while Choptuik [40] developed a numerical study for a massless scalar field considering a family of solutions with the property that a critical parameter, p * , indicates the formation of black holes. Since then several works studied the critical behavior and the properties of the gravitational collapse of scalar fields [41][42][43][44][45][46][47][48].…”
Section: Generalized Brans-dicke Theoriesmentioning
confidence: 99%
“…The possibilities of end product of a scalar field collapse, whether a naked singularity or a black hole, has also been explored in [6]. The variants of scalar field collapse and its consequences are demonstrated in [7,8,9,10,11,12,13,14,15,16,17] (see also [18,19,20,21,22,23]).…”
Section: Introductionmentioning
confidence: 99%
“…One can also reduce the scalar field cosmology equations to a known type of equation whose solution has already been developed. In [29,32] we can see a method in which the Klein-Gordon equation which describes the dynamics of the scalar field is transformed to a first order non-linear differential equation. This equation immediately leads to the identification of some exact classes of scalar field potentials V (φ) for which the field equations can be solved exactly and there by obtaining analytical expressions for a(t), φ(t) and q(t) .…”
Section: Introductionmentioning
confidence: 99%